What Kind of Patients Receive Inpatient and Day-Hospital Treatment in Departments of Psychosomatic Medicine and Psychotherapy in Germany? - Doering, Stephan; Herpertz, Stephan; Hofmann, Tobias; Rose, Matthias; Imbierowicz, Katrin; Geiser, Franziska; Croy, Ilona; Weidner, Kerstin; Rademacher, Jörg; Michalek, Silke; Morawa, Eva; Erim, Yesim; et al. (Psychotherapy and Psychosomatics, 2023)
Introduction: Germany is one of the few countries with a medical specialty of psychosomatic medicine and psychotherapy and many treatment resources of this kind. Objective: This observational study describes the psychosomatic treatment programs as well as a large sample of day-hospital and inpatients in great detail using structured diagnostic interviews. Methods: Mental disorders were diagnosed according to ICD-10 and DSM-IV by means of Mini-DIPS and SCID-II. In addition to the case records, a modified version of the CSSRI was employed to collect demographic data and service use. The PHQ-D was used to assess depression, anxiety, and somatization. Results: 2,094 patients from 19 departments participated in the study after giving informed consent. The sample consisted of a high proportion of "complex patients"with high comorbidity of mental and somatic diseases, severe psychopathology, and considerable social and occupational dysfunction including more than 50 days of sick leave per year in half of the sample. The most frequent diagnoses were depression, somatoform and anxiety disorders, eating disorders, personality disorders, and somato-psychic conditions. Conclusions: Inpatient and day-hospital treatment in German university departments of psychosomatic medicine and psychotherapy is an intensive multimodal treatment for complex patients with high comorbidity and social as well as occupational dysfunction.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Day-hospital; Diagnosis; Inpatient treatment; Psychosomatic medicine; Psychotherapy